Structural Characterization and Anticoagulant Activity of a 3-O-Methylated Heteroglycan From Fruiting Bodies of Pleurotus placentodes - Yin, Zhen-Hua; Liu, Xiao-Peng; Wang, Jin-Mei; Xi, Xue-Feng; Zhang, Yan; Zhao, Rui-Lin; Kang, Wen-Yi (Frontiers in Chemistry, 2022)
A 3-O-methylated heteroglycan (PPp-W), with a molecular weight of 27.4 kDa, was obtained from fruiting bodies of Pleurotus placentodes. PPp-W was irregular curly sheets with a triple-helix conformation and composed of mannose (17.56%), glucose (6.37%), galactose (44.89%) and fucose (1.22%) with a certain amount of 3-O-methyled galactose. Further studies showed PPp-W contained →6)-α-D-Galp-(1→, →6)-3-O-Me-α-D-Galp-(1→and →2, 6)-α-D-Galp-(1→ as main chain, partially substituted at O-2 and O-6 by non-reducing ends of β-D-Manp-(1→ and β-L-Fucp-(1→ with a small amounts of α-1,3-linked-Glcp in backbone. In vitro coagulation test, PPp-W could significantly prolong APTT and TT to show anticoagulant ativity, which showed that PPp-W was expected to be applied in anticoagulant.